Repeatability and Relationship of Incidence and Severity Measures of Scab of Wheat Caused by Fusarium graminearum in Inoculated Nurseries - Groth, J V (Plant disease, 1999)
Breeders of hard red spring wheat (Triticum aestivum) are attempting to incorporate resistance to scab, caused by Fusarium graminearum. In artificially inoculated, replicated field plots, 37 wheat entries (inbred lines or cultivars) were evaluated for 3 years and an additional 60 entries for 2 of the 3 years for incidence (percent spikes infected), severity (percent infected spikelets within infected spikes), and disease index (percent infected spikelets in 50-spike sample). From year to year, entries had similar index values, with coefficients of determination (r 2) ranging from 0.59 to 0.78, with a mean of 0.73. Entries appeared slightly more similar from year to year for incidence than for severity, although both measures of disease had highly significant r 2 values. Incidence and severity were highly correlated in the wheat germ plasm examined; r 2 values in single years ranged from 0.51 to 0.67, with a mean of 0.64. A representative subset of 22 entries was included for a fourth year. None of the measures of disease in year 4 correlated with their counterparts in any of the first 3 years. This loss of repeatability may have been caused by severe lodging or by high temperatures during the evaluation period that accelerated disease progress and wheat maturity during year 4. Incidence and severity remained correlated in year 4 (r 2 = 0.60)